1999
DOI: 10.1001/archsurg.134.12.1360
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Regulation of Neutrophil Function in Surgical Inflammation

Abstract: Background: Morbidity and even mortality correlate closely with major injury that causes a systemic inflammatory response. Cytokines and bioactive molecules present at the inflammatory site induce this response and regulate neutrophil proinflammatory responses. The CXC chemokines, important for neutrophil recruitment and activation, include interleukin 8 (IL-8), granulocyte chemotactic protein 2 (GCP-2), and epithelial cell-derived neutrophil attractant 78 (ENA-78). They induce neutrophil responses via 2 cell-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…The chemokine receptors CXCR1 and CXCR2 are central for many PMN functions. 29 Although some reports have shown that in vitro treatment with cytokines and/or bacterial products could downregulate CXCR1 and CXCR2 expression on human neutrophils, 23,30 studies with patients with sepsis, confirming our data, showed that expression of CXCR1, the high-affinity receptor for IL-8, were not altered in sepsis. 31,32 Most neutrophil chemoattractants recognize membrane GPCR on the leukocytes and, as a result of receptor activation by the chemoattractant, a complex sequence of signaling events are triggered, inducing profound alterations in cytoskeleton dynamics and activating signaling pathway, allowing neutrophils to develop motile, adhesive, phagocytic, and antimicrobial responses.…”
Section: Discussionsupporting
confidence: 88%
“…The chemokine receptors CXCR1 and CXCR2 are central for many PMN functions. 29 Although some reports have shown that in vitro treatment with cytokines and/or bacterial products could downregulate CXCR1 and CXCR2 expression on human neutrophils, 23,30 studies with patients with sepsis, confirming our data, showed that expression of CXCR1, the high-affinity receptor for IL-8, were not altered in sepsis. 31,32 Most neutrophil chemoattractants recognize membrane GPCR on the leukocytes and, as a result of receptor activation by the chemoattractant, a complex sequence of signaling events are triggered, inducing profound alterations in cytoskeleton dynamics and activating signaling pathway, allowing neutrophils to develop motile, adhesive, phagocytic, and antimicrobial responses.…”
Section: Discussionsupporting
confidence: 88%
“…PMN are recruited to sites of bacterial invasion by GPC chemoattractants. There they take part in immune surveillance and the control of infection (35). In vitro, LTs, chemokines, and other chemoattractants can act individually to recruit PMN (14, 15, 36 -39).…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 is a chemokine and belongs to a group of mediators with the ability for leukocyte recruitment and activation at the site of injury [39]. Recently, increases in IL-8 mRNA expression was observed in the early posttraumatic period which preceded down-regulation of the innate immune system, and the expression was correlated to increased mortality [40].…”
Section: Sirsmentioning
confidence: 99%